The call to complain : antecedents to complaint behaviour (telecommunications industry). - Lim, An Qi. (2011)
Given the benefits of appropriate complaint management, this study focuses on understanding the antecedents to consumer complaint behaviour, in order to help companies maintain their competitive advantage over competitors.